In situ split liver transplantation with celiac trunk allocation: technical evolution and outcomes supporting right-sided preservation - Kanani, Fahim; Mahajna, Naheel; Gravetz, Aviad; Gurevich, Micheal; Lubezky, Nir; Ovadya, Ronli; Nesher, Eviatar (Frontiers in Surgery, 2026)
BackgroundSplit liver transplantation (SLT) expands the donor pool, but optimal arterial configuration remains debated. We report outcomes of right-sided in situ SLT with systematic celiac trunk preservation with the right graft.MethodsRetrospective Multicentre analysis of 36 consecutive adult recipients of right-sided split grafts (2015–2025) with celiac trunk preservation. Primary outcomes included vascular complications, patient/graft survival, and comparison with published benchmarks.ResultsRecipients (mean age 54.0 ± 12.6 years, 53% male) underwent SLT for HCV (30.6%), NASH (19.4%), and other etiologies. Major vascular complications occurred in 12/36 (33%) of cases, though life-threatening events remained uncommon: HAT 2.8%, postoperative PVT 5.6%, arterial stenosis 5.6%. Biliary complications occurred in 25% (ischemic 8.3%, technical 17%). Patient survival was 86% at 1 year and 81% at 3 years. Reoperation rate was 47%, primarily for biliary complications (17%) and intra-abdominal abscess (14%). Retransplantation rate was 11%.ConclusionRight-sided SLT with celiac trunk preservation achieves excellent vascular outcomes, with both HAT (2.8%) and PVT (5.6%) rates meeting international benchmarks. These results strongly support this configuration as the preferred technical approach for in situ split liver transplantation.